Dosimetric Comparison between Intensity Modulated Radiation Therapy (IMRT) and Three-Dimensional Conformal Radiation Therapy (3DCRT) in Mid Lower esophageal Carcinoma: An Analytical Observational Study - Tali, Tavseef Ahmad; Amin, Fiza; Khan, Aijaz Ahmad; Sofi, Shahid Rashid; Sofi, Mushtaq Ahmad; Khan, Mohsin Rehman (Indonesian Society for Cancer Chemoprevention, 2022)
Esophageal cancer (EC) is a common cancer with high mortality because of its rapid progression and poor prognosis. One of the most successful therapies for EC is radiotherapy. Two recently created radiation methods are intensity-modulated radiotherapy (IMRT) and three-dimensional conformal radiotherapy (3D-CRT). In terms of target coverage, dose homogeneity, and lowering toxicity to healthy organs, IMRT is thought to be superior to 3D-CRT. These benefits haven't been proven in the treatment of EC, though. This study was performed to investigate if intensity modulated radiation therapy (IMRT) offers a better planning target volume (PTV) coverage and/or lower dose to organs at risk in comparison to three-dimensional conformal radiation therapy (3DCRT). 30 patients with locally advanced histo-pathologically proven mid and lower oesophageal carcinoma, not reaching gastro-esophageal junction were treated with chemoradiation using IMRT technique. 3DCRT plans were generated for those 30 patients. The IMRT and 3DCRT plans were compared in terms of PTV coverage and doses to organs at risk. Our results revealed that IMRT is better than 3DCRT comparing PTV coverage and doses to organs at risk having statistically significant difference between both techniques (p<0.001). As for the organs at risk (OAR), the V20 for the IMRT plans delivered lesser lung volume irradiation also the mean dose to the heart and the V30 were both higher in the 3DCRT plans.Keywords: esophageal cancers (ECs), Organs at risk (OAR), Intensity modulated radiation therapy (IMRT), Three-dimensional conformal radiation therapy (3DCRT), Planned target volume (PTV).